Analisis Strategi Pemasaran Toko Kelontong Bu Yus Terhadap Keputusan Pembelian Konsumen Masyarakat Sebokarang - Vivi Alviani; Yunita Fitri Wahyuningtyas (Universitas Muhammadiyah Metro, 2025)
The formulation of the research problem is how the marketing strategy carried out by Toko Bu Yus towards consumer purchasing decisions. The purpose of the study was to determine the marketing strategy of Toko Bu Yus towards consumer purchasing decisions in the Sebokarang community. The research method used was qualitative by collecting data through observation, interviews and documentation. The results showed that Toko Bu Yus had implemented a marketing strategy, namely complete products sold, affordable prices offered, strategic store locations, friendly service. Based on the score value on the IFAS matrix, internal conditions have greater strength to overcome weaknesses. Based on the EFAS score matrix, Toko Bu Yus has not utilized all existing opportunities optimally. So the SWOT quadrant obtained is in quadrant II, namely diversification strategy. This situation describes a company that faces serious challenges and threats. Implementation of strategies for consumer purchasing decisions through attractive promotions, Increasing accessibility, Relationships with suppliers. The conclusion is that the strategy used must be improved again, the opportunities owned have not been utilized optimally. The weakness with the highest value is the absence of a digital marketing strategy and dependence on supplies from certain suppliers. The suggestion is First, Toko Bu Yus must maintain product quality, service and price stability in order to remain satisfying for consumers. Second, we must increase promotional activities to be better known to the public and increase people's purchasing decisions. Third, we need to take advantage of digital marketing opportunities that exist in the current era